PERSUASIVE COMMUNICATION OF THE #BUBARKANMUI MOVEMENT - Tayibnapis, Radita Gora; Muqsith, Munadhil Abdul; Sembada, Windhiadi Yoga (JWP (Jurnal Wacana Politik), 2023)
The campaign narrative for the dissolution of the Indonesian Ulema Council (MUI) invited many comments from netizens on social media to develop into a digital social movement to urge the Indonesian Ulema Council (MUI) to be dissolved because one of its members was arrested by the police regarding the issue of terrorism. This news had become a trending topic on Twitter and threatened the existence of MUI as a forum for Islamic community organizations in Indonesia. To analyze these problems, researchers used the Network Society theory with a quantitative approach and the Social Network Analysis (SNA) method to analyze it. This study aims to analyze actors’ conversations in voicing new social movements through the #BubaranMUI hashtag. Through the spread of a communication network on the hashtag #BubarkanMUI, it was found to be an effort of a digital social movement that was echoed by political actors through a single Twitter account as well as building fake accounts as alter egos for intermediaries and network close relations to spread negative comments about MUI and spread communication networks as a public call through media atwitter and gain support from Twitter users to disband the MUI.